Impella 5.0 therapy as a bridge-to-decision option for patients on extracorporeal life support with unclear neurological outcomes. (30th April 2019) - Bernhardt, Alexander M; Zipfel, Svante; Reiter, Beate; Hakmi, Samer; Castro, Liesa; Söffker, Gerold; Kluge, Stefan; Lubos, Edith; Rybczinski, Meike; Grahn, Hanno; Schrage, Benedikt; Becher, Peter Moritz; et al.
Abstract: OBJECTIVES: Peripheral venoarterial extracorporeal life support (ECLS) for the treatment of cardiogenic shock has shown to improve survival but is associated with complications. However, if the patient cannot be weaned from ECLS, their therapy options are limited. Although durable left ventricular assist device implantation might be an option in such cases, an unclear neurological outcome is often a contraindication. We hypothesize that Impella 5.0 therapy provides sufficient circulatory support while avoiding ECLS-related complications, thereby allowing for an adequate evaluation of a patient's neurological state and facilitating further treatment options. METHODS: We retrospectively reviewed data from 22 ECLS patients (mean age 56.5 ± 10.7 years) with an unclear neurological status who underwent Impella 5.0 implantation between January 2016 and July 2018 in our institution. Neurological status was evaluated on a daily basis using the cerebral performance category score and the modified Rankin scale. RESULTS: Sixteen patients (72.7%) were resuscitated before ECLS implantation and 13 patients (59.1%) had acute myocardial infarction. The mean duration on ECLS before Impella 5.0 implantation was 9.3 ± 1.7 days. All patients were successfully weaned from ECLS by Impella 5.0 implantation via the axillary artery. The mean duration on Impella 5.0 was 16.3 ± 4.7 days. In surviving patients, both quantitative measurements of cerebral performance improved after 30 days compared to the baseline ( P < 0.01). Six patients (27.3%) were bridged to a durable left ventricular assist device. In 9 patients (40.9%), myocardial function recovered during Impella 5.0 support and the device was successfully explanted. The 30-day survival rate was 68.2%. CONCLUSIONS: Impella 5.0 support provides a bridge-to-decision option for patients following ECLS implantation and leads to left ventricular unloading. It allows further evaluation of a patient's neurological situation and facilitates further therapy. About two-thirds of patients survived with acceptable neurological outcomes.